Politics Of The Nation And Madrasah’s policy - Abd. Rahman Mas’ud (Badan Litbang dan Diklat Kementerian Agama RI, 2013)
Pendekatan sejarah dan politik digunakan demi pemahaman kemunculan kebijakan madrasah dalam sejarah Indonesia. Pendekatan ini dipercaya mampu memetakan hubungan antara politik dan kelahiran pendidikan madrasah. Dalam masa awal pembentukan, pendidikan madrasah tidak diakui oleh Belanda dalam masa pemerintahannya sebagai penjajah di Indonesia. Ini menghasilkan kurangnya aspirasi keagamaan dan pendidikan kaum Muslim terhadap pemerintahan Belanda. Kebijakan yang menentang madrasah mulai berubah dalam masa penjajahan Jepang yang memungkinkan kaum Muslim untuk berekspresi secara politik. Dalam era memasuki kemerdekaan, periode yang mengakomodasi ruang politik muncul dengan menyuarakan kaum Muslim, dengan bukti pembentukan Menteri Agama pada tanggal 3 Januari, 1946. Di masa inilah madrasah secara penuh dipayungi oleh kementerian agama. Hingga kini, madrasah dan pesantren belum diakui dalam sistem pedidikan nasional. Situasi ini berlangsung hingga tahun 1960an. Sejalannnya dengan masa orde baru, pihak pemerintah bersikap akomodatif terhadap aspirasi umat Islam, yang secara spesifik berhubungan dengan pendidikan. Maka dari itu pendidikan madrasah mulai masuk dan terintegrasi menjadi sistem pendidikan nasional. Pembentukan SKB Tiga Menteri pada tahun 1975 (kementerian agama, kementerian pendidikan dan kebudayaan, dan kementerian dalam negeri) dan pasal no. 2 tahun 1989 yang menyangkut sistem pendidikan nasional, mampu dilihat sebagai sebuah proses integrasi tahap awal. Madrasah adalah sekolah umum yang bersifat keislaman yang dibentuk oleh Kementerian Agama. Perihal ini berlangsung sampai terbentuknya pasal no. 20 tahun 2003 yang menyangkut sistem pendidikan nasional. Dalam periode ini, pendidikan madrasah dan sekolah umum memiliki level derajat yang sama. Historical and political approaches were used to understand the birth of the madrasah’s policy in throughout Indonesia’s history . These approaches were considered to be able to map the relationship between politics and the birth of madrasah education policy. In the early period, when the nation was controlled by the Dutch colonial government, madrasah education was not included in the Dutch educational system. This was a result of the lack of fulfillment of religious and educational aspirations of Muslims by the Dutch government. Policy against madrasah began to change during the Japanese occupation where Islam began to gain a space for political expression. Entering post-independence, a political period known as the political accommodation emerged as the nation provided enough space for Islam to existed, marked by the establishment of the Ministry of Religious Affairs on January 3rd, 1946. This was when madrasah fell under the Ministry of Religious Affairs. Until this point, madrasah and pesantren were not included in the national education system. This situation continued until the 1960s. During the New Order Regime, the government was very accommodative to Muslim aspirations, in particular those related to Islamic education. Thus madrasah education entered and was integrated into the national education system. The birth of SKB Tiga Menteri (Three Ministers decree) on 1975 (Minister of Religious Affairs, Minister of Education and Culture, and the Ministry of Home Affairs) and Law No. 2 Year 1989 concerning the national education system could be seen as the early integration of madrasah into the national education system. Madrasah is a public school distinctively of Islamic religion held by the Ministry of Religious Affairs. It was like this until the birth of Law No. 20 Year 2003 concering the National Education System. In this period, madrasah education is equivalent to education in public schools.